Nurses' care for the mother-baby binomial in the Stork Network in the light of ecosystem thinking (Research, Society and Development, 2020)
Objective: to know and analyze the care that the nurse develops for the mother-baby binomial in the Rede Cegonha, in a city in the south of RS, in the light of ecosystemic thinking. Methodology: Descriptive, exploratory study with a qualitative approach. Data collection occurred in the months of October / November 2016 through semi-structured interviews, for the analysis content analysis was used in the Minayo thematic analysis modality. Results: The care actions provided to the mother-baby binomial are developed in primary, secondary and tertiary health care, contemplating, care aimed at the health / vitality of the concept of maternal and child health, as well as the prevention of maternal and child mortality. . This care developed in the light of Ecosystem Thinking, allows transformations and new models of action. Conclusion: The use of ecosystemic principles in shaping the Network in question, even if incipient, among the services, is essential to achieve the integrality and unity / totality of care for the mother-baby binomial.